1996
DOI: 10.1039/ft9969200131
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for different copper species in precursors of copper–cerium oxide catalysts for hydrogenation reactions. An X-ray diffraction, EPR and X-ray photoelectron spectroscopy study

Abstract: Conditions for preparing copper-cerium mixed oxides by coprecipitation have been examined. X-Ray diffraction (XRD), electron paramagnetic resonance (EPR) and X-ray photoelectron spectroscopy (XPS) were used to characterize the oxides calcined at different temperatures up to 1073 IS. In all cases, a solid solution is formed by the insertion of Cu2+ ions in substitutional Paper 5/04920B;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(19 citation statements)
references
References 16 publications
(2 reference statements)
5
13
0
1
Order By: Relevance
“…The spectrum of the Cu/CeO 2 sample is characterized by a Cu 2p 3/2 band at 933.8 eV and shake-up satellites at ca. 944.0 eV, typical characteristics of Cu 2+ species in CuO-like phase [20,48,[66][67][68][69][70]. The above assignments are in line with the XRD findings, which revealed the formation of the corresponding metal oxides in M/CeO 2 samples (Table 2).…”
Section: Surface Characterization (Xps Analysis)supporting
confidence: 76%
“…The spectrum of the Cu/CeO 2 sample is characterized by a Cu 2p 3/2 band at 933.8 eV and shake-up satellites at ca. 944.0 eV, typical characteristics of Cu 2+ species in CuO-like phase [20,48,[66][67][68][69][70]. The above assignments are in line with the XRD findings, which revealed the formation of the corresponding metal oxides in M/CeO 2 samples (Table 2).…”
Section: Surface Characterization (Xps Analysis)supporting
confidence: 76%
“…In the case of Rh2+, Anderson and co-workers [31] have reported that rhodium ions on ceria surface were stabilized against reduction and aggregation by incorporation of the Rh cations to cerium oxide surface layers, resulting in a high metal dispersion. The same phenomenon has been observed with Cu2' ions on ceria surface [2,32]. Lamonier et al [2] have demonstrated that the insertion of Cu2' into the ceria lattice occurred during the coprecipitation step of catalyst preparation, resulting the creation of anionic vacancies upon calcination.…”
Section: Determination Of Copper Surface Areamentioning
confidence: 56%
“…The same phenomenon has been observed with Cu2' ions on ceria surface [2,32]. Lamonier et al [2] have demonstrated that the insertion of Cu2' into the ceria lattice occurred during the coprecipitation step of catalyst preparation, resulting the creation of anionic vacancies upon calcination. Four different copper species attributed to monomers, dimers, clusters and small particles of CuO have been found.…”
Section: Determination Of Copper Surface Areamentioning
confidence: 56%
See 1 more Smart Citation
“…Para tanto se deve considerar a não influência da temperatura de calcinação do catalisador na quantidade de cobre superficial na segunda razão e a grande variação de cobre exposto na primeira. Além do mais, Lamonier et alo [58] estudando catalisadores do tipo Ce-Cu-O por XPS também constatou a migração do cobre contido no "bulk" da céria com o aumento da temperatura de calcinação. * Diminuição da razão superficial com relação à razão nominal .…”
Section: Investigação Da Composiçãounclassified